Genetic Deletion of mGlu3 Metabotropic Glutamate Receptors Amplifies Ischemic Brain Damage and Associated Neuroinflammation in Mice - Mastroiacovo, Federica; Zinni, Manuela; Mascio, Giada; Bruno, Valeria; Battaglia, Giuseppe; Pansiot, Julien; Imbriglio, Tiziana; Mairesse, Jerome; Baud, Olivier; Nicoletti, Ferdinando (Frontiers in Neurology, 2021)
Backgroud: Type-3 metabotropic glutamate (mGlu3) receptors are found in both neurons and glial cells and regulate synaptic transmission, astrocyte function, and microglial reactivity. Here we show that the genetic deletion of mGlu3 receptors amplifies ischemic brain damage and associated neuroinflammation in adult mice. An increased infarct size was observed in mGlu3−/− mice of both CD1 and C57Black strains 24 h following a permanent occlusion of the middle cerebral artery (MCA) as compared to their respective wild-type (mGlu3+/+ mice) counterparts. Increases in the expression of selected pro-inflammatory genes including those encoding interleukin-1β, type-2 cycloxygenase, tumor necrosis factor-α, CD86, and interleukin-6 were more prominent in the peri-infarct region of mGlu3−/− mice. In contrast, the expression of two genes associated with the anti-inflammatory phenotype of microglia (those encoding the mannose-1-phosphate receptor and the α-subunit of interleukin-4 receptor) and the gene encoding the neuroprotective factor, glial cell line-derived neurotrophic factor, was enhanced in the peri-infarct region of wild-type mice, but not mGlu3−/− mice, following MCA occlusion. In C57Black mice, the genetic deletion of mGlu3 receptors worsened the defect in the paw placement test as assessed in the contralateral forepaw at short times (4 h) following MCA occlusion. These findings suggest that mGlu3 receptors are protective against ischemic brain damage and support the way to the use of selective mGlu3 receptor agonists or positive allosteric modulators in experimental animal models of ischemic stroke.